Antibacterial activity of liposome containing curry plant essential oil against Bacillus cereusin rice. Issue 2 (15th July 2016) - Cui, Haiying; Li, Wei; Lin, Lin
Abstract: We herein evaluated the antibacterial effect of curry plant EO, a natural antibacterial agent, on B. cereus . The curry plant EO was encapsulated into liposomes to improve the chemical stability of EO and its active time. By a thin‐film dispersion method, soy lecithin, in combination with cholesterol, were used to prepare liposomes at various curry plant EO concentrations. The optimal formula for preparing liposome is a curry plant EO concentration of 5.0 mg/ml. The average particle size of liposomes containing curry plant EO was 196.6 nm with a PDI of 0.218 and the entrapment efficiency was 56.34%. The optimal liposomes containing curry plant EO gave a zeta potential of −31.1 mV. Besides, liposome‐encapsulated curry plant EO exhibited efficient antimicrobial activity for B. cereus in rice. Practical applications: As a natural and safe antibacterial agent, curry plant EO shows an excellent antibacterial effect on B. cereus in rice. The concept in the present study may be useful in the future to deliver a variety of antimicrobials for the treatment of various infections caused by bacteria or other organisms. Hence, the antimicrobial agent has broad prospect in the field of food preservation.